SIMBOL KARAKTER GAY DALAM GENRE BOYS LOVE DI KOTA PADANG - Febrizani, Nissya; Erwin, Erwin; Setiawati, Sri (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
This research explores the interpretations of LGBTQ+ students regarding Boys love content, a genre featuring romantic relationships between male characters. Despite attracting fans from diverse backgrounds, the genre's interpretations often stem from the perspective of heterosexual women, creating a paradox in LGBTQ+ representation. Through in-depth interviews with LGBTQ+ individuals, fujoshi (female Boys love fans), and heterosexual individuals, this study discusses how symbols of love, romance, and LGBTQ+ identity in the storyline are perceived by the residents of Padang City. The research results unveil a diverse and intricate understanding of LGBTQ+ characters, relationships, and symbols in Boys love.Furthermore, this research elucidates the crucial role played by symbols such as clothing, hairstyles, and accessories in shaping perceptions and identities within the LGBTQ+ community. These findings offer valuable insights into the impact of media representations on understandings of same-sex identities and relationships in societies still contending with traditional norms. The study also acknowledges generational differences in the interpretation of Boys love and how this content influences emotions, identity, and relationships within the LGBTQ+ community in Padang City. This research contributes to the comprehension of the Boys love phenomenon and its influence on LGBTQ+ individuals in Padang City, providing a foundation for understanding the complexity of LGBTQ+ representation in popular culture.